Réponses

2012-11-20T20:20:19+01:00

4 x^2+12 x+9=(7-4 x)^2

4 x^2+12 x+9=16 x^2-56 x+49

-12 x^2+68 x-40=0

12 x^2-68 x+40=0

4 (3 x^2-17 x+10)=0

3 x^2-17 x+10=0

 

deux solutions (utilise delta) :

 

x= (17+racine(169))/6)

x=(17-racine(169))/6)

 

Tu simplifies ce qui donne :

x= 5

x= 2/3

2012-11-20T20:47:15+01:00

bonsoir

(2x+3)²=(7-4x)²

(2x+3)² - (7-4x)² =0   forme de a²-b² = (a+b)(a-b) 

(2x+3+7-4x)(2x+3-7+4x) = 0

(-2x+10)(6x-4)= 0

deux solutions

soit -2x+10 = 0   alors x = 5

ou  6x-4 = 0   alors x = 2/3